Designs of the world (British Museum pattern books., 2011)
A sourcebook of hundreds of designs drawn from the work of artists and craftsmen throughout time, from the Pacific cultures of Oceania to the rich and varied heritage of Ancient Greece. It includes an informative introduction and a selection of illustrated patterns.